Application Of Vegetative Biofilter With Tricking Filter Technique On Water Supply With High Sulphur Content To Increase Seed Production Of Traditional Nile Tilapia Fish Hatchery In Tegal Randu Village, Klakah District, Lumajang. - Agoes Soeprijanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
Tegal Randu Village, Klakah District has high potency of natural resources in the form of Ranu Klakah, where in this place there are Keramba Jaring Apung (KJA) to have business of conducting nile tilapia fish ± 300 slots. One of the obstaclesin this business is conducting nile tilapia fish seed supply which sus-pends from other area, in limited number and there is no guarantee of this quality. In Tegal Randu and its surrounding areas there is no business of nile tilapia fish hatchery. Furthermore, water irrigation of Ranu Klakah contains high rate of sulfur so its quite vulnerable to business of fish hatchery. The purposes of this program were a) to give an education, train about nila fish hatchery b) education, train in the field of biofilter technique to be able to repair and improve the water quality for the nila fish hatchery. c) management of ecofriendly fishery conducting and d) to create new employment. Method which is used in this program is Counselling, Training, Discussion and demonstration of filter in the form of vegetative biofilter with trickling filter. The Result of this activity are a) Biofilter Vegetative System and Biodrum Filter Trickling b) the increasing of society enthusiasm to business of fish conducting and nile tilapia fish hatchery by the construction of some pool. This activity drives society enthusiasm so it needs to be continued with further development activities.